High time resolution spectroscopy studies of the explosive decomposition of silver azide - Aduev B. P.; Aluker E. D.; Belokurov G. M.; Zakharov Yu. A. Yuriy Aleksandrovich; Krechetov A. G. (1996, 1996)
Title screen